Low cost sample preparation method using ultrasound for the determination of environmentally critical elements in seaweed - Gustavo Gohlke; Vitoria H. Cauduro; Emanuele Frozi; Luana F. Rocha; Giancarlo R. Machado; Alessandra S. Henn; Yang Tao; Marcia F. Mesko; Erico M. M. Flores (Ultrasonics Sonochemistry, 2024)
In this study, ultrasound (US) was evaluated for As, Cd, Pb, Mn, Sr and V extraction from seaweed samples. The following parameters of ultrasound-assisted extraction (UAE) using an US bath were: frequency (25 to 130 kHz), amplitude (30 to 100%), temperature (30 to 80 °C), sample mass (50 to 200 mg), extractant concentration (1 to 3 mol L−1 of HNO3) and treatment time (5 to 30 min). Acoustic density and power density distribution were calculated using the calorimetric method and mapping of the acoustic pressure distribution was also evaluated. The optimized UAE conditions were 200 mg of sample in 10 mL of 2 mol L−1 HNO3 and 30 min of sonication in a 25 kHz US bath (37.2 ± 4.0 W L−1) at 70% of amplitude and 70 °C. Analytes were quantified using inductively coupled plasma mass spectrometry and results were compared with values obtained using “silent” conditions (magnetic or mechanical stirring at 500 rpm, and without stirring), and a reference method based on microwave-assisted wet digestion (MAWD). The UAE method demonstrated the best extraction efficiency (higher than 95%) for all analytes, especially for As, Cd and V, with lower standard deviations (up to 5%) and lower blank values in comparison with the silent conditions. The proposed UAE method was more advantageous than the reference method, being faster, simpler, safer, more environmentally friendly, and with higher detectability (lower limits of quantification, from 0.0033 to 1.34 µg g−1). In addition, negligible blank values were obtained for UAE and no interference were observed in the determination step. Furthermore, the optimized UAE method was applied for Antarctic seaweed samples and comparison with results obtained by MAWD was satisfactory. In this sense, UAE is demonstrated to be a suitable option for sample preparation of seaweed samples and further determination of environmentally critical elements avoiding the use of concentrated reagents as in the MAWD reference method.